(untitled) (Al-Academy, 2021)
The form imposes its importance in the structure of the artwork through its indication of the type of relationship between the artist and his external world in all its aspects, as well as its manifestation of artistic and aesthetic values, and the multiplicity of experimental means of expression that include the artist’s feelings and imagination. The form is also a recording of the events in their temporal and spatial circumstances, and in that it is of value in directing his artistic discourse with the aim of influencing the recipient with its connotations and emotional states. Horses in the drawings of Amer Al-Obaidi, and the research came within two frameworks: The first framework is the methodological framework that represents us the research problem, its importance, purpose and limits, as well as defining terminology. Artists throughout history and the second topic, in which we dealt with the experience of Amer Al-Obeidi and his method of drawing horse shapes. As well as the research procedures that included the research community, its sample, its tools and its methodology, then we followed that by analyzing the samples, results and conclusions